ARTICULATORY AND ACOUSTIC CHARACTERISTICS OF SPEECH SOUNDS: THE ROLE OF SPECH ORGANS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article "Articulatory and Acoustic Features of Sounds: Speech Organs" provides a comprehensive overview of the anatomical structures involved in speech production and their functional roles in articulating sounds. It begins by categorizing the speech organs into three main systems: respiratory, phonatory, and articulatory, highlighting how each contributes to sound generation. The article details key organs such as the lungs, larynx, and tongue, explaining their specific functions in producing different speech sounds. It further explores articulatory features like place and manner of articulation, as well as voicing, which define how sounds are produced. Acoustic features such as frequency, amplitude, duration, and formants are also examined, emphasizing their importance in distinguishing speech sounds and conveying meaning. The interaction between articulatory and acoustic features is discussed, particularly the concept of coarticulation, which illustrates how sounds can influence one another in connected speech. Overall, the article underscores the complexity of speech production and its significance in linguistics, speech therapy, and artificial intelligence. It serves as a valuable resource for understanding the mechanics of human communication, providing insights into both the biological and acoustic dimensions of speech.